2005
DOI: 10.1097/01.pec.0000159067.09573.f1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Pain Intensity and Associated Distress in Children Aged 4-18 Years on Admission, Discharge, and One-Week Follow Up to Emergency Department

Abstract: A greater proportion of children report high intensity of distress from pain than of pain intensity itself when in the ED. Only a small proportion of children received analgesics during the visit to the ED and only slightly more on discharge. Although pain seems to resolve by 1 week, distress is less likely to have resolved. More attention needs to be paid both to pain children are experiencing in the ED and equally to the accompanying distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
1
21
2
3
Order By: Relevance
“…A great disparity was observed in the literature review. The study by Kircher et al found similar results to those of our study and was conducted in patients with musculoskeletal pain (6%), 12 in contrast to the studies by Benini et al, 13 done in headache patients, and by C. Johnston et al, 14 in multiple diseases, where pain was assessed in more than a half of patients (57% and 71%, respectively). In our study, and contrary to what is recommended in the literature, pain was assessed without using validated scales.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…A great disparity was observed in the literature review. The study by Kircher et al found similar results to those of our study and was conducted in patients with musculoskeletal pain (6%), 12 in contrast to the studies by Benini et al, 13 done in headache patients, and by C. Johnston et al, 14 in multiple diseases, where pain was assessed in more than a half of patients (57% and 71%, respectively). In our study, and contrary to what is recommended in the literature, pain was assessed without using validated scales.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, and contrary to what is recommended in the literature, pain was assessed without using validated scales. In relation to pain management in the PED, our results were observed to be somewhat better than in other studies 12,13,16 and similar to those observed by C. Johnston 14 and O'Donnell, 17 which included limb trauma cases and where only 39% and 49% of patients received analgesia during their stay in the emergency room. In our study, like in the ones by Rogovik 16 and Benini et al, 13 analgesia was prescribed at the time of discharge to most patients; whereas, in the studies by C. Johnston et al 14 and Kircher et al, 12 it was only prescribed to 9% and 24% of patients, respectively.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Pain is a common reason for seeking health care [1][2][3] and adequate pain management is a basic human right 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Numerous studies indicate that inadequate pain management during medical care can have many detrimental short and long-term effects, [4][5][6][7] and the World Health Organization has advocated for optimal pain treatment for all. 8 Children's pain in the ED remains poorly managed despite an increase in pain research over the past decade.…”
Section: Introductionmentioning
confidence: 99%